Voltage- and Calcium-Dependent Inactivation of Calcium Channels in Lymnaea Neurons - Gera, Shalini (The Rockefeller University Press, 1999)
Ca(2+) channel inactivation in the neurons of the freshwater snail, Lymnaea stagnalis, was studied using patch-clamp techniques. In the presence of a high concentration of intracellular Ca(2+) buffer (5 mM EGTA), the inactivation of these Ca(2+) channels is entirely voltage dependent; it is not influenced by the identity of the permeant divalent ions or the amount of extracellular Ca(2+) influx, or reduced by higher levels of intracellular Ca(2+) buffering. Inactivation measured under these conditions, despite being independent of Ca(2+) influx, has a bell-shaped voltage dependence, which has often been considered a hallmark of Ca(2+)-dependent inactivation. Ca(2+)-dependent inactivation does occur in Lymnaea neurons, when the concentration of the intracellular Ca(2+) buffer is lowered to 0.1 mM EGTA. However, the magnitude of Ca(2+)-dependent inactivation does not increase linearly with Ca(2+) influx, but saturates for relatively small amounts of Ca(2+) influx. Recovery from inactivation at negative potentials is biexponential and has the same time constants in the presence of different intracellular concentrations of EGTA. However, the amplitude of the slow component is selectively enhanced by a decrease in intracellular EGTA, thus slowing the overall rate of recovery. The ability of 5 mM EGTA to completely suppress Ca(2+)-dependent inactivation suggests that the Ca(2+) binding site is at some distance from the channel protein itself. No evidence was found of a role for serine/threonine phosphorylation in Ca(2+) channel inactivation. Cytochalasin B, a microfilament disrupter, was found to greatly enhance the amount of Ca(2+) channel inactivation, but the involvement of actin filaments in this effect of cytochalasin B on Ca(2+) channel inactivation could not be verified using other pharmacological compounds. Thus, the mechanism of Ca(2+)-dependent inactivation in these neurons remains unknown, but appears to differ from those proposed for mammalian L-type Ca(2+) channels.